A micro/nano-multiscale hierarchical structure strategy to fabricate highly conducting films for electromagnetic interference shielding and energy storage. Issue 16 (21st March 2023) - Wang, Beibei; Zhang, Weiye; Sun, Jingmeng; Lai, Chenhuan; Ge, Shengbo; Guo, Hongwu; Liu, Yi; Zhang, Daihui
Abstract : A micro/nano-multiscale hierarchical structure strategy is used to fabricate films. A leaf-like structure with AgNWs and MXene results in a conductive 3D network. TOCNFs in the middle layer endow the films with excellent mechanical properties. Abstract : Ultrathin, strong, flexible, and conductive materials have garnered considerable attention in foldable wearable electronics and electromagnetic interference (EMI) shielding. However, their preparation remains challenging to simultaneously achieve desired high-performance electrochemical and EMI properties. Herein, we describe a micro/nano-multiscale hierarchical structure strategy to fabricate TEMPO-oxidized cellulose nanofibrils (TOCNFs)/Ti3 C2 T x MXene/silver nanowire (AgNW) hybrid films via a facile alternating vacuum-filtration process, followed by hot-pressing. The micro/nanoscale design enabled the films to exhibit excellent EMI and electrochemical properties simultaneously. Specifically, the FM2Ag2 (TOCNFs/Ti3 C2 T x /AgNW = 1 : 2 : 2) hybrid film exhibited outstanding mechanical properties with a tensile strength of 85.63 ± 7.24 MPa, excellent electrical conductivity of 1.29 × 10 7 S m −1, superior EMI shielding effectiveness (EMI SE) of 45.57 dB, and high SSE/ t of 26 014.52 dB cm 2 g −1 . Moreover, it maintained a high areal and specific capacitance of 110.7 mF cm −2 and 77.6 F g −1 at 10 mV s −1, respectively, accompanied by impressive stability with 92.4% capacitance retention after 10 000 cycles. This study proposes a novel and facile micro/nano-multiscale hierarchical structure strategy to effectively balance the electrochemical and EMI properties. This paves the way for the fabrication of robust multifunctional films for potential applications in precise instruments and next-generation electronics.